Pressurized IntraPeritoneal Aerosol Chemotherapy – Practical aspects. Issue 6 (June 2017) - Hübner, M.; Grass, F.; Teixeira-Farinha, H.; Pache, B.; Mathevet, P.; Demartines, N.
Abstract: Introduction: Pressurized Intraperitoneal Aerosol Chemotherapy (PIPAC) has been introduced as novel treatment for peritoneal carcinomatosis. Only proper patient selection, stringent safety protocol and careful surgery allow for a secure procedure. We hereby report the essentials for safe implementation. Methods: All consecutive procedures within 20 months after PIPAC implementation were analyzed with regards to practical and surgical aspects. Special emphasis was laid on modifications of technique and safety measures during the implementation process with systematic use of a dedicated checklist. Further, surgical difficulty was documented by use of a visual analogue scale (VAS). Results: 127 PIPAC procedures were performed in 58 patients from January 2015 until October 2016. 81% of patients had at least one previous laparotomy. Median operation time was 91 min (87–103) for the first 20 cases, 93 min (IQR 88–107) for PIPAC21-50, and 103 min (IQR 91–121) for the following 77 procedures. Primary and secondary non-access occurred in 3 patients (2%), all of them having prior hyperthermic intraperitoneal chemotherapy (HIPEC). Using open Hasson technique, one single bowel lesion occurred, which was the only intraoperative complication. One 5 mm and another 10/12 mm trocar were used in 88% of procedures while additional trocars were needed in 12%. No leak of cytostatics was observed and no procedure needed to be stopped. VAS for overall difficulty of the procedure was 3 ± 2.4, and 3 ± 2.9 and 3 ± 2.5, respectively, for abdominal access and intraoperative staging. Conclusions: With standardized surgical approach and dedicated safety checklist, PIPAC can be safely introduced in clinical routine with minimal learning curve.